You Can't Measure That…Can You? How a Catholic Seminary Approaches the Question of Measuring Growth in Human and Spiritual Formation. Issue 2 (November 2021) - Hoesing, Paul; Hogan, Ed
The question of measuring growth in human and spiritual formation in Catholic seminaries has a history. In this article, we walk through three recent stages of that history to illuminate the potential of current approaches and clarify what still remains to be done.